ViSim: a user-friendly graphical simulation tool for performance analysis of MANET routing protocols - Saquib, Nazmus; Sakib, Md. Sabbir Rahman; Pathan, Al-Sakib Khan (Pergamon, 2011)
The task of simulation is often complicated, and naive users often look for relatively easier solutions. In many cases, simulations are done with no visual output which makes them non-attractive. In this paper, we present ViSim; a new simulation tool that has a user-friendly graphical interface. ViSim could be useful for researchers, students, teachers in their work, and for the demonstration of various wireless network scenarios on computer screens. It could make the task of simulation more exciting and enhance the interest of the users by avoiding the need to use a complex command-only text interface. ViSim is not a simulation engine, rather it calls ns-2 simulations in the background and makes the task easy for the users to visualize the simulation in a Windows environment. Though ViSim is mainly a simulation demonstration tool, any user with knowledge of ns-2 and Tcl scripting also has the provision to make the necessary modifications and rapid configuration for any other MANET routing scenario. Using our simulation tool, we measured the performances of several Mobile Ad-hoc Network (MANET) routing protocols. In this paper, we present the performance analysis of three prominent MANET routing protocols (DSDV, DSR and AODV) using our tool. Details of the various features of ViSim, brief descriptions of the selected routing protocols and their comparisons, and details about the experiments performed and the results obtained are presented in this work.